Revision of the troglomorphic genus Troglostygnopsis Šilhavý, 1974 (Opiliones, Laniatores, Stygnopsidae) - Cruz-López, Jesús A.; Francke, Oscar F. (European Journal of Taxonomy, 2021)
In the present paper, we have made a taxonomic revision of the previously monotypic genus Troglostygnopsis Šilhavý, 1974. Based on the revision of diverse material, the genus is rediagnosed and the type species, Troglostygnopsis anophthalma Šilhavý, 1974 is redescribed. The new species Troglostygnopsis kalebi sp. nov. is described from specimens collected in a cave in Chiapas, Mexico, and this species is compared with T. anophthalma. A final discussion on some troglobitic genera of Stygnopsidae is addressed.